2012
DOI: 10.1063/1.4748290
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous stimulated Raman, Brillouin, and electron-acoustic scattering reveals a potential saturation mechanism in Raman plasma amplifiers

Abstract: In a Raman plasma amplifier, the aim is to create plasma conditions in which Raman backscattering is the fastest growing instability, outrunning all competing effects so that it is possible to amplify and compress a laser beam to unprecedented unfocused intensities by utilizing that instability. However, achieving high efficiencies via this scheme has proven very difficult experimentally. Recent data show the simultaneous occurrence of stimulated Raman scattering (SRS), stimulated Brillouin scattering (SBS), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…40,41 The obtained spectrum resembles strongly the one presented here for the 80 fspulse, i.e., the SRS-and SBS-signatures do not overlap. The presence of SRS and SBS is due to the simultaneous excitation of the modes and their competition might indicate a saturation mechanism.…”
Section: Discussionsupporting
confidence: 74%
“…40,41 The obtained spectrum resembles strongly the one presented here for the 80 fspulse, i.e., the SRS-and SBS-signatures do not overlap. The presence of SRS and SBS is due to the simultaneous excitation of the modes and their competition might indicate a saturation mechanism.…”
Section: Discussionsupporting
confidence: 74%
“…The first experimental observation of this competitive phenomenon was made by Walsh et al (1984) in which they observed that the quenching of SRS plasma waves were strongly correlated to the initiation of SBS ion waves. Recently, it has been found experimentally that for plasma based laser amplifiers, it is essential to study SRS and SBS simultaneous at relativistic laser power (Turnbull et al, 2012;Weber et al, 2013). Therefore, the motivation of the present work is to understand the effect of the coexistence on the growth, saturation, and the reflectivity of SRS and SBS including the effect of relativistic selffocusing of intense Gaussian laser beam.…”
Section: Introductionmentioning
confidence: 97%
“…5,6 For very high intensities, Raman and Brillouin processes might be even mixed. [7][8][9] Even though scattering is initiated more quickly in the Raman case, utilizing ion modes for backscattering may prove to be more robust and less demanding with respect to the plasma parameters.…”
Section: Introductionmentioning
confidence: 98%